Palynological study of the fossil floras of the Lower Miocene and early Middle Miocene of the Pichucalco region, Chiapas, Mexico - Palacios Chavez, Rodolfo; Rzedowski, Jerzy (Instituto de Ecología, A.C., 1993)
Marine sedimentary rocks of northern Chiapas, near the limits of Tabasco and Veracruz, sampled along the road from Huimanguillo to Presa de Malpaso, at altitudes between 300 and 500 m, are subjected to a palynological and paleoecological study. 663 different microfossils are identified, mostly pollen and spores, in these sedimentary rocks. Present ecological conditions of the sampled area are those of a tropical evergreen forest with Terminalia, Vochysia, Brosimum, Dialium and Manilkara among other trees, and of related communities as palm forest, tropical savanna and Quercus oleoides forest. The studied stratigraphic column embraces Lower Miocene to Middle Miocene; the microfossils found and the palynological spectra show that most pollen grains belong to genera of the family Juglandaceae, mainly of the Engelhardtia-Oreomunnea complex, which is dominant in most of the sediments studied. Also quantitatively important are pollen grains of Picea, Quercus, Pinus and Melastomataceae, as well as spores of Cyatheaceae and Polypodiaceae. High percentages of Engelhardtia-Oreomunnea pollen grains and abundant spores of Cyathea and Alsophila indicate a paleoenvironment dominated mostly by Engelhardtia-Oreomunnea forest, growing in a coastal montane area of relatively cool and very wet climate. A comparative study of modern pollen rains for some warm and temperate zones of Mexico is included, mainly of Engelhardtia-Oreomunnea forests and of other types of vegetation related to the palynoflora found in the analyzed sediments.